OKUMA BECERİLERİNE YÖNELİK MADDELERİ YANITLAMA HIZLARINI YORDAYAN ÖZELLİKLERİN BELİRLENMESİ. - AYDOĞAN, İzzettin; GELBAL, Selahattin (Mehmet Akif Ersoy University Journal of Education Faculty)
The current study aimed to determine the features predicting students' response speed for items related the reading skills. The study group of the study is comprised of 5232 students aged 15 years participating in the PISA 2015 program. The data of the study were obtained over the PISA 2015 program and analyzed by using the regression model based on the genetic algorithms method estimation. Analyzes were carried out using the R program. It was intended to perform a feature selection process for the regression model, which consisted of the variables that best predicted response speed for items related the reading skills with the method of genetic algorithms. The results obtained revealed that the variables of gender, number of books at home, language spoken at home, reading skills, number of actions and weekly lesson hours for reading skills at school significantly predicted the students' response speed for items related the reading skills. The variation in the variables whose prediction power was found to be significant was understood to lead to a significant variation in students' response speed for items measuring the reading skills. It was observed that the variables that statistically significantly predicted students' response speed explained 8.53% of the variability in response speed.